Positive electrode material sagger and manufacturing method based on spray granulation technology
The manufacture of the lithium battery positive electrode material cassette through spray granulation technology solves the problems of large mold wear, difficult to control product uniformity, poor finish and serious lithium absorption, and achieves the high stability, long life and low production costs of the cassette.
Patent Information
- Application Number
- CN202411950681.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-18
AI Technical Summary
During the production process, the existing lithium battery positive electrode material scaffolds have problems such as large mold wear, difficult product uniformity, poor finish and serious lithium absorption, resulting in high production costs and degradation of the performance of the positive electrode material.
The squeegee manufacturing method based on spray granulation technology is adopted, and the squeegee with high stability and many recycles are prepared by designing dry mix and slurry, and spray dry granulation and dry press forming processes.
It effectively reduces mold wear, improves the uniformity and finish of the product, reduces lithium absorption, extends the service life of the cassette, and significantly reduces the production cost of the cathode material.
Smart Images

Figure CN119638394A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium battery sagger manufacturing, and in particular relates to a positive electrode material sagger and a manufacturing method based on spray granulation technology. Background Art
[0002] Lithium battery positive electrode material sagger is an important container used in the sintering process of lithium battery positive electrode materials. In the preparation process of lithium battery positive electrode materials, the sagger serves as a container for high-temperature sintering, carrying and protecting the positive electrode materials, while providing suitable reaction conditions to ensure the quality and performance of the positive electrode materials.
[0003] Lithium battery cathode material saggers need to have the characteristics of not polluting the fired finished material, having good corrosion resistance, thermal shock stability and atmosphere adaptability. With the development of new lithium battery cathode materials, the performance requirements for sagger materials are getting higher and higher.
[0004] Cordierite has the advantages of small thermal expansion coefficient and good thermal shock stability, but its low strength and low load softening temperature limit its performance; mullite has the characteristics of good high temperature performance and high mechanical strength. Therefore, mullite-cordierite composite kiln furniture materials have received attention. By adding matrix materials such as calcined α-Al2O3 powder, sagger materials with good sintering properties, mechanical properties and thermal shock stability can be prepared.
[0005] At present, the industry usually makes saggers by dry mixing the above raw materials and then aging, molding and firing. The above method of making saggers has the following problems: 1. The mold is worn out. Mullite, cordierite, magnesia spinel, etc. are usually used as the main raw materials for the production of saggers. These raw materials have different particle sizes, high hardness, and are mostly irregular in shape. They will cause a large degree of wear on the mold during the pressing process. The iron impurities generated by mold wear are mixed in the sagger, which may contaminate the positive electrode material when the sagger is used.
[0006] 2. The uniformity of sagger products is difficult to control: The heterogeneity of the particle size, shape and density of the powder raw materials will lead to kinetic differences in the mixing and compacting process, causing particle segregation. This segregation phenomenon will reduce the macroscopic uniformity of the material, and the microstructural uniformity will also be destroyed after sintering. In the production of conventional mullite-cordierite saggers, large particles are usually used as a skeleton structure to maintain the overall stability and thermal shock resistance of the product. The problem of particle segregation has always been a difficult point to control in the industry, because particle segregation will lead to uneven material mixing, affect the mechanical strength and thermal stability of the product, and cause cracks in the sagger products during thermal cycling.
[0007] 3. Poor finish of sagger products: If the large-particle material is not fully wrapped in the matrix, it will form protrusions on the surface of the product, resulting in poor surface finish and easier erosion. These substances will contaminate the positive electrode material of the lithium battery, resulting in a decrease in the performance of the positive electrode material and even causing safety hazards.
[0008] 4. Obvious lithium absorption: The sagger is in contact with the positive electrode material of the lithium battery. The positive electrode material of the lithium battery, especially the lithium ions therein, will penetrate from the contact surface, causing the sagger to absorb lithium. The pore size of the refractory sagger has a significant effect on the lithium ion penetration behavior. The higher the apparent porosity, the worse its anti-penetration performance is usually. High porosity means more penetration channels, which increases the possibility of lithium ion penetration. In order to improve the quality and stability of the positive electrode material of the lithium-ion battery, it is usually necessary to select a refractory sagger with a smaller pore size. However, in conventional mullite-cordierite saggers, in order to maintain better thermal shock stability, they usually have a larger porosity, which leads to obvious penetration of lithium ions into the sagger. In the first 1-2 productions of some positive electrode material manufacturers with new saggers, the positive electrode material will lose lithium in a large range due to the absorption of lithium by the sagger, thus affecting the performance of the positive electrode material.
[0009] It is precisely because of the above-mentioned problems that saggers are consumables in the production process of lithium battery positive electrode materials. Taking the saggers used in the production of lithium cobalt oxide as an example, most of them have a lifespan of about 15 times. Through process parameter regulation or for different types of positive electrode materials, the lifespan will not change much. Therefore, they need to be replaced frequently. Therefore, how to improve the lifespan of saggers and the quality of the positive electrode materials produced is still worth studying. Summary of the invention
[0010] In view of the shortcomings of the prior art, one of the objects of the present invention is to provide a sagger manufacturing method based on the spray granulation technology to reduce the wear on the sagger manufacturing mold.
[0011] Another object of the present invention is to provide a positive electrode material sagger, which is prepared by the above-mentioned preparation method. The obtained sagger has good stability and a high number of recycling uses, and can significantly reduce the production cost of the positive electrode material.
[0012] In order to achieve the above object, the present invention adopts the following technical solutions: On the one hand, the present invention provides a method for manufacturing a sagger based on a spray granulation technology, comprising the following steps: S1. Material A preparation: dry-mix potassium aluminum silicate (KAlSiO4), mullite, cordierite and aluminum titanate until uniform to obtain a first dry-mixed material; The organic binder is dissolved in water, and the mixture is added to the first dry mixed material and stirred evenly, and then allowed to stand for a period of time to obtain a slurry material A, wherein mullite, cordierite and aluminum titanate are all medium-sized particles, and potassium aluminum silicate is a small-sized particle material; S2, material B configuration: cordierite, talc, zirconium dioxide, kaolin and aluminum oxide are dry-mixed in proportion until uniform, to obtain a second dry-mixed material, wherein cordierite is a medium-sized material, and talc, zirconium dioxide, kaolin and aluminum oxide are all small-sized materials; Dissolve the inorganic binder in water, add the second dry mixed material and stir evenly to obtain a slurry-like material B; S3, dilute material B with water, then add material A, stir evenly to obtain a mixed slurry; S4, granulating the mixed slurry by spray drying to obtain a granular material; S5, preparing a sagger body by dry pressing the granular material; S6. Sinter the sagger body at high temperature to obtain a positive electrode material sagger.
[0013] Furthermore, in step S1, in the first dry mixture, the particle sizes of mullite, cordierite and aluminum titanate are 100 meshes, and the particle size of potassium aluminum silicate is 300 meshes.
[0014] Furthermore, in step S1, the proportions in material A are calculated by mass fraction as follows: 45%-60% mullite, 5%-8% aluminum titanate, 5-6% potassium aluminum silicate, 3%-5% cordierite, 1-2% organic binder, and 35%-40% water.
[0015] Furthermore, the organic binder is sodium carboxymethyl cellulose and / or yellow dextrin; and the inorganic binder is sodium tripolyphosphate.
[0016] Furthermore, in step S2, in the second dry blend, the particle size of cordierite is 100 mesh, the particle sizes of talc, alumina and zirconium dioxide are all 325 mesh, and the particle size of kaolin is 250 mesh.
[0017] Furthermore, in step S2, the proportions in material B are calculated by mass fraction as follows: cordierite 15%-20%, talc 10%-20%, zirconium dioxide 3%-8%, aluminum oxide 20%-25%, kaolin 8%-10%, inorganic binder 1-2%, and water 35%-45%.
[0018] Furthermore, in step S3, when preparing the mixed slurry, the mass ratio of material A, material B, and water is 1:0.8-1.2:0.4-0.6 respectively.
[0019] Furthermore, in step S4, during the spray drying granulation process, the air inlet temperature of the spray dryer is controlled at 200°C-300°C, the atomization pressure is controlled at 0.5-1.5 MPa, and the particle size of the produced material is 0.5-1 mm.
[0020] Furthermore, in step S4, after spray drying and granulation, the moisture content of the granules is 5%-6%.
[0021] Furthermore, in step S6, during high temperature sintering, the kiln temperature in the sintering stage is 1330-1390°C.
[0022] On the other hand, the present invention provides a positive electrode material sagger, which is prepared by the above sagger preparation method.
[0023] The above formula of the present invention is based on the improvement of the formula system of conventional mullite-cordierite sagger, combined with spray granulation technology, to reduce the manufacturing cost of the sagger and increase the service life of the sagger; the batching principle of the present invention is as follows: In the preparation process of material A of the present invention, mullite is used as the main material, and a small amount of aluminum titanate, potassium aluminum silicate and cordierite are added. After mullite of medium particle size is mixed with potassium aluminum silicate of small particle size, the potassium aluminum silicate is adsorbed on the surface of mullite due to the small amount and small particles, and contacts with a small amount of cordierite and aluminum titanate. A small amount of water and sodium carboxymethyl cellulose added later can make potassium aluminum silicate completely adsorbed on the surface of mullite, and cover the mullite with a small amount of cordierite and aluminum titanate to form a stable core-shell structure.
[0024] In the preparation process of material B of the present invention, cordierite, talc and aluminum oxide are used as main materials, and a small amount of zirconium dioxide and kaolin are added. The medium-sized cordierite and small-sized materials are evenly dispersed in water through the inorganic binder sodium tripolyphosphate to form a slurry.
[0025] After material A and material B are mixed with water, the core-shell structure is evenly distributed in the entire slurry of material B, and the KAlSiO4 adsorbed on the surface of mullite only contacts with a small amount of cordierite.
[0026] The final spray drying will use mullite as the base core, with KAlSiO4, aluminum titanate and a small amount of cordierite scattered on the outside, and then coated with B material on the outside to form a core-shell structure of 0.5-1mm particles.
[0027] During firing, KAlSiO4 coated on the surface of mullite reacts with mullite particles to form needle-shaped potassium alumina-rich silicate, which connects the large mullite particles together, thereby giving the product better strength. Based on the above research and development concepts and principles, the ratio of mullite to KAISiO4 in the present invention is controlled at 10:1 as the optimal ratio.
[0028] Zirconium dioxide (ZrO2) in material B acts as a toughening agent. While enhancing the overall toughness of the product, it can also form microcracks inside the material due to the volume expansion caused by its phase change.
[0029] When KAlSiO4 contacts a small amount of cordierite, it will form phases such as magnesium aluminum spinel, which has good high temperature performance. However, when KAlSiO4 contacts a large amount of cordierite, it will generate a low melting point phase. The presence of the above-mentioned microcracks can effectively prevent the inner layer KAlSiO4 from reacting with the outer layer cordierite in large quantities, thereby stably generating phases such as magnesium aluminum spinel, so that the product has good high temperature performance. At the same time, microcracks will make the finished product have better toughness, and thus better thermal shock stability.
[0030] After material A and material B are mixed and sintered, mullite and needle-shaped potassium alumina-rich silicate (KAlSiO4 is generated by the reaction of mullite particles) will form a grid structure, and cordierite, talc, and Al2O3 will form a eutectic phase dispersed in the above grid structure. The microcracks formed by ZrO2 are combined with the stabilizing effect of aluminum titanate and the toughening effect of talc to achieve multiple toughening; the mesh structure + multiple toughening achieves isotropic thermal expansion performance and enhances high-temperature stability, and enhances the thermal shock stability of sagger products. In addition to the main structure mentioned above, the present invention also considers the following issues when designing the formula to achieve the purpose: Homogenization of thermal expansion coefficient: By adjusting the ratio of the main components of mullite, cordierite, talc and alumina, the overall thermal expansion coefficient of the composite material can be optimized, the internal stress caused by temperature changes can be reduced, and the thermal shock stability of the material can be improved.
[0031] Uniformity of crystal structure: A small amount of KAlSiO4 is introduced into the A material, and the K + The action of ions on the cordierite lattice can shorten the lattice constant in the c-axis direction and increase the lattice constant in the a-axis direction, thereby adjusting the lattice parameters of cordierite and making its thermal expansion behavior in different directions more consistent, thus achieving isotropy of the thermal expansion coefficient.
[0032] High temperature phase stability: In the present invention, aluminum titanate is dispersed at the junction of material A and material B. After firing, it will play a bridging role at the junction of the grid structure and the eutectic, and give the product good dimensional stability with its low thermal expansion coefficient. 3+ The smaller the ion radius, the larger the thermal vibration, which may lead to structural deformation. In order to improve the high-temperature stability of aluminum titanate, the present invention forms a solid solution by adding zirconium oxide (ZrO2), suppresses excessive thermal vibration of aluminum oxide octahedron, reduces lattice distortion, thereby stabilizing the lattice structure of aluminum titanate, enhancing its phase stability at high temperatures, and improving the mechanical properties and thermal shock resistance of the material.
[0033] The present invention solves various problems in the prior art by using spray granulation technology on the basis of formula optimization, which are as follows: Reduce mold wear: The present invention uses spray granulation technology to manufacture granular materials with a particle size of about 0.5-1 mm, and utilizes the filling and wrapping effect of small-size materials to avoid the edges and corners of relatively large particles of mullite and cordierite, so that the mold is almost not worn when the sagger blank is pressed, which can maximize the service life of the mold and reduce the manufacturing cost of the sagger; at the same time, it can also improve the surface finish of the sagger and improve the corrosion resistance of the sagger surface.
[0034] Avoid particle segregation during the green compacting process: The present invention uses spray granulation technology to ensure the consistency of each particle after granulation while ensuring highly uniform mixing, thereby avoiding the possibility of segregation during the subsequent green compacting process. Even if the product formula is not optimized, the quality of the sagger can be improved.
[0035] Compared with the traditional formula and process, the beneficial effects of the present invention are as follows: 1. Small wear on the mold: The process implemented by the present invention includes the use of spray granulation technology, followed by compression molding, wherein the granulated particles are round or nearly round in shape. Due to the flow characteristics and reduced friction area of the round particles, the wear rate of the mold during the compression molding process is effectively reduced, thereby reducing mold wear and extending the mold life, directly reducing production costs and improving economic benefits; at the same time, the round particles have good flow properties, which helps to improve the filling efficiency and molding speed of compression molding.
[0036] 2. Uniform products: In the present invention, uniform mixing of raw materials is achieved by using spray granulation technology, which ensures the homogeneity of materials during the granulation stage. This method effectively solves the segregation phenomenon caused by particle size differences during the transportation and pressing process after mixing in the traditional multi-level particle size matching system, thereby avoiding the problem of uneven structure and performance of ceramic products caused by this, and ensuring the uniformity of product performance, including mechanical strength, thermal shock stability and chemical stability; 3. Good finish: During the pressing process of the present invention, the particle structure formed by spray granulation will be re-compacted, and the microstructure of the product after firing significantly reflects the initial particle characteristics of the raw material. The raw material of the present invention adopts 100 mesh and finer particles. During the sintering process, the high specific surface area of the fine particles promotes the rapid sintering of the material and realizes the uniform densification of the microstructure, thereby ensuring that the product is delicate and tight, has good finish, and ensures that the surface of the product is not easily corroded and slag is not easily removed.
[0037] 4. Small lithium absorption problem: The smaller pore size of the product of the present invention helps to improve the material's anti-permeability ability and limit the diffusion path of lithium ions; the uniform distribution of pore size is also crucial to controlling the penetration of lithium ions, avoiding the preferential penetration of lithium ions along specific paths (such as larger pores) to form a dendritic penetration network, thereby greatly reducing the lithium absorption phenomenon of the sagger.
[0038] 5. Strong corrosion resistance: The present invention adopts KAlSiO4 material. Since potassium (K) and lithium (Li) are in the same main group in the periodic table, the compounds they form have similar chemical properties, so the interaction with the positive electrode material of the lithium battery is weak, which can better resist the corrosion of the positive electrode material to the sagger during high-temperature sintering and long-term operation. Due to the dual advantages of surface and chemical stability, the sagger products of the present invention have better resistance to corrosion by positive electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 The present invention is a flow chart of the sagger manufacturing method based on the spray granulation technology. DETAILED DESCRIPTION
[0040] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with examples. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments.
[0041] like Figure 1 As shown, the present invention provides a method for manufacturing a sagger based on a spray granulation technology, comprising the following steps: S1, material A configuration: potassium aluminum silicate (KAlSiO4), mullite, cordierite and aluminum titanate are dry-mixed until uniform to obtain a first dry-mixed material, wherein mullite, cordierite and aluminum titanate are all medium-sized particles, and potassium aluminum silicate is a small-sized particle material; Dissolve the organic binder in water, add the first dry mixed material and stir evenly, then let it stand for a period of time to obtain a slurry material A; S3, material B configuration: dry-mix cordierite, talc, zirconium dioxide, kaolin and aluminum oxide in proportion until uniform, to obtain a second dry-mixed material, wherein cordierite is a medium-sized material, and talc, zirconium dioxide, kaolin and aluminum oxide are all small-sized materials; Dissolve the inorganic binder in water, add the second dry mixed material and stir evenly to obtain a slurry-like material B; S3, dilute material B with water, then add material A, stir evenly to obtain a mixed slurry; S4, granulating the mixed slurry by spray drying to obtain a granular material; S5, preparing a sagger body by dry pressing the granular material; S6. Sinter the sagger body at high temperature to obtain a positive electrode material sagger.
[0042] Embodiment 1: S1, A material configuration: Dry mixing: 5 kg of 300-mesh potassium aluminum silicate (KAlSiO4), 50 kg of 100-mesh mullite, 3 kg of 100-mesh cordierite and 5 kg of 100-mesh aluminum titanate were dry mixed for 20 minutes until uniform, to obtain a first dry mixed material; Dissolve sodium carboxymethyl cellulose: add 35.5 kg of water into a stirring bucket, slowly add 1.5 kg of sodium carboxymethyl cellulose, and stir until it is completely dissolved to obtain a sodium carboxymethyl cellulose solution; Wet mixing: Add the first dry mix into the sodium carboxymethyl cellulose solution, stir evenly and let stand for 10 minutes to promote water absorption and uniformity, and obtain slurry A material; S2, B material configuration: Dry mixing: 16 kg of 100-mesh cordierite, 12 kg of 325-mesh talc, 4 kg of 325-mesh zirconium dioxide, 9 kg of 250-mesh kaolin and 22 kg of 325-mesh aluminum oxide were mixed and dry mixed until uniform to obtain a second dry mixed material; Dissolve sodium tripolyphosphate: add 36 kg of water into a mixing bucket, slowly add 1 kg of sodium tripolyphosphate, and stir until it is completely dissolved to obtain a sodium tripolyphosphate solution; Wet mixing: Add the second dry mix into the sodium tripolyphosphate solution and stir evenly to obtain a slurry-like material B; S3, material A, material B and water are mixed in a ratio of 1:1:0.5, material B is diluted with water, and then material A is added, and stirred evenly to obtain a mixed slurry; S4, granulating the mixed slurry through a spray dryer to obtain a granular material; The equipment parameters of the spray dryer are controlled as follows: Inlet air temperature: 250℃ Air outlet temperature: 80℃ Atomization pressure: 1MPa Spray tower diameter: 2 meters Sprayer Type: Two-fluid nozzle Drying time: until the moisture content of the particles drops to 5%-6% Granule drying: Dry the wet granules after spray granulation in a dryer, control the drying temperature not to exceed 100°C, until the moisture content of the granules reaches 5%-6%.
[0043] S5, preparing a sagger body by dry pressing the granular material; The green body is formed by dry pressing machine, and the forming pressure is 20MPa. Molding speed: 2-3 times / minute The size of the sagger after forming: customized according to needs, such as 330x330x100mm opening; S6. Sintering the sagger body at high temperature to obtain a positive electrode material sagger; specifically, placing the sagger body in a roller kiln, preheating, sintering, and cooling to obtain a sagger product, wherein the kiln temperature in the sintering stage is 1330-1390°C.
[0044] Embodiment 2: S1, A material configuration: Dry mixing: 4.7 kg of 300-mesh potassium aluminum silicate (KAlSiO4), 47 kg of 100-mesh mullite, 3.5 kg of 100-mesh cordierite and 6.5 kg of 100-mesh aluminum titanate were dry mixed for 20 minutes until uniform to obtain a first dry mixed material; Dissolve sodium carboxymethyl cellulose: add 36.8 kg of water into a stirring bucket, slowly add 1.5 kg of sodium carboxymethyl cellulose, and stir until it is completely dissolved to obtain a sodium carboxymethyl cellulose solution; Wet mixing: Add the first dry mixed material into the sodium carboxymethyl cellulose solution, stir evenly and let stand for 10 minutes to promote water absorption and uniformity, and obtain slurry material A; S2, B material configuration: Dry mixing: 15 kg of 100-mesh cordierite, 11 kg of 325-mesh talc, 5 kg of 325-mesh zirconium dioxide, 8 kg of 250-mesh kaolin and 25 kg of 325-mesh aluminum oxide were mixed and dry mixed until uniform to obtain a second dry mixed material; Dissolve sodium tripolyphosphate: add 35 kg of water into a mixing bucket, slowly add 1 kg of sodium tripolyphosphate, and stir until it is completely dissolved to obtain a sodium tripolyphosphate solution; Wet mixing: add the second dry mix into the sodium tripolyphosphate solution and stir evenly to obtain a slurry-like material B; S3, material A, material B and water are mixed in a ratio of 1:1:0.5, material B is diluted with water, and then material A is added, and stirred evenly to obtain a mixed slurry; S4, granulating the mixed slurry through a spray dryer to obtain a granular material; The equipment parameters of the spray dryer are controlled as follows: Inlet air temperature: 250℃ Air outlet temperature: 80℃ Atomization pressure: 1MPa Spray tower diameter: 2 meters Sprayer Type: Two-fluid nozzle Drying time: until the moisture content of the particles drops to 5%-6% Granule drying: Dry the wet granules after spray granulation in a dryer, and control the drying temperature not to exceed 100°C until the moisture content of the granules reaches 5%-6%.
[0045] S5, preparing a sagger body by dry pressing the granular material; The green body is formed by dry pressing machine, and the forming pressure is 20MPa. Molding speed: 2-3 times / minute The size of the sagger after forming: customized according to needs, such as 330x330x100mm opening; S6. Sintering the sagger body at high temperature to obtain a positive electrode material sagger; specifically, placing the sagger body in a roller kiln, preheating, sintering, and cooling to obtain a sagger product, wherein the kiln temperature in the sintering stage is 1330-1390°C.
[0046] Embodiment 3: S1, A material configuration: Dry mixing: 5 kg of 300-mesh potassium aluminum silicate (KAlSiO4), 50 kg of 100-mesh mullite, 3 kg of 100-mesh cordierite and 5.5 kg of 100-mesh aluminum titanate were dry mixed for 20 minutes until uniform, to obtain a first dry mixed material; Dissolve sodium carboxymethyl cellulose: add 35 kg of water into a stirring bucket, slowly add 1.5 kg of sodium carboxymethyl cellulose, and stir until it is completely dissolved to obtain a sodium carboxymethyl cellulose solution; Wet mixing: Add the first dry mix into the sodium carboxymethyl cellulose solution, stir evenly and let stand for 10 minutes to promote water absorption and uniformity, and obtain slurry A material; S2, B material configuration: Dry mixing: 15 kg of 100-mesh cordierite, 10 kg of 325-mesh talc, 6 kg of 325-mesh zirconium dioxide, 10 kg of 250-mesh kaolin and 22 kg of 325-mesh aluminum oxide were mixed and dry mixed until uniform to obtain a second dry mixed material; Dissolve sodium tripolyphosphate: add 36 kg of water into a mixing bucket, slowly add 1 kg of sodium tripolyphosphate, and stir until it is completely dissolved to obtain a sodium tripolyphosphate solution; Wet mixing: Add the second dry mix into the sodium tripolyphosphate solution and stir evenly to obtain a slurry-like material B; S3, material A, material B and water are mixed in a ratio of 1:0.9:0.5, material B is diluted with water, and then material A is added, and stirred evenly to obtain a mixed slurry; S4, granulating the mixed slurry through a spray dryer to obtain a granular material; The equipment parameters of the spray dryer are controlled as follows: Inlet air temperature: 250℃ Air outlet temperature: 80℃ Atomization pressure: 1MPa Spray tower diameter: 2 meters Sprayer Type: Two-fluid nozzle Drying time: until the moisture content of the particles drops to 5%-6% Granule drying: Dry the wet granules after spray granulation in a dryer, and control the drying temperature not to exceed 100°C until the moisture content of the granules reaches 5%-6%.
[0047] S5, preparing a sagger body by dry pressing the granular material; The green body is formed by dry pressing machine, and the forming pressure is 20MPa. Molding speed: 2-3 times / minute The size of the sagger after forming: customized according to needs, such as 340x340x100mm opening; S6. Sintering the sagger body at high temperature to obtain a positive electrode material sagger; specifically, placing the sagger body in a roller kiln, preheating, sintering, and cooling to obtain a sagger product, wherein the kiln temperature in the sintering stage is 1330-1390°C.
[0048] The mullite-cordierite saggers in Examples 1-3 and the prior art were subjected to sagger preparation, performance testing and application testing. The test results are the average values of multiple tests, and the results are as follows:
[0049] It can be seen from the above table that the use of the formula and method of the present invention to prepare positive electrode material saggers not only reduces mold wear, prolongs the service life of the mold, and reduces manufacturing costs, but also the prepared positive electrode material saggers have obvious technical advantages in mechanical strength, porosity, and number of cycles, and have achieved good practical benefits in the actual production process of the factory.
[0050] The above embodiments are only used to illustrate the present invention, but not to limit the present invention. Although the present invention is described in detail with reference to the embodiments, it should be understood by those skilled in the art that various combinations, modifications or equivalent substitutions of the technical solutions of the present invention do not depart from the spirit and scope of the technical solutions of the present invention, and should be included in the scope of the claims of the present invention.
Claims
1. A method for manufacturing a sagger based on spray granulation technology, characterized in that: The following steps are involved: Material A preparation: dry-mix potassium aluminum silicate, mullite, cordierite and aluminum titanate until uniform to obtain a first dry-mixed material; The organic binder is dissolved in water, and the mixture is added to the first dry mixed material and stirred evenly, and then allowed to stand for a period of time to obtain a slurry material A, wherein mullite, cordierite and aluminum titanate are all medium-sized particles, and potassium aluminum silicate is a small-sized particle material; Material B configuration: cordierite, talc, zirconium dioxide, kaolin and aluminum oxide are dry-mixed in proportion until uniform to obtain a second dry-mixed material, wherein cordierite is a medium-sized material, and talc, zirconium dioxide, kaolin and aluminum oxide are all small-sized materials; Dissolve the inorganic binder in water, add the second dry mixed material and stir evenly to obtain a slurry-like material B; Add water to dilute material B, then add material A, stir evenly to obtain a mixed slurry; The mixed slurry is granulated by spray drying to obtain a granular material; The granular material is formed into a sagger body by dry pressing; The sagger green body is sintered at high temperature to obtain a positive electrode material sagger.
2. The sagger manufacturing method based on spray granulation technology according to claim 1 is characterized in that: In the first dry blend, the particle sizes of mullite, cordierite and aluminum titanate are 100 meshes, and the particle size of potassium aluminum silicate is 300 meshes.
3. The sagger manufacturing method based on spray granulation technology according to claim 1 is characterized in that: The proportions in material A are calculated by mass fraction as follows: mullite 45%-60%, aluminum titanate 5%-8%, potassium aluminum silicate 5-6%, cordierite 3%-5%, organic binder 1-2%, and water 35%-40%.
4. The sagger manufacturing method based on spray granulation technology according to claim 1 is characterized in that: The organic binder is sodium carboxymethyl cellulose and / or yellow dextrin; the inorganic binder is sodium tripolyphosphate.
5. The sagger manufacturing method based on spray granulation technology according to claim 1 is characterized in that: In the second dry blend, the particle size of cordierite is 100 mesh, the particle sizes of talc, aluminum oxide and zirconium dioxide are all 325 mesh, and the particle size of kaolin is 250 mesh.
6. The sagger manufacturing method based on spray granulation technology according to claim 1 is characterized in that: The proportions in material B are calculated by mass fraction as follows: cordierite 15%-20%, talc 10%-20%, zirconium dioxide 3%-8%, aluminum oxide 20%-25%, kaolin 8%-10%, inorganic binder 1-2%, and water 35%-45%.
7. The sagger manufacturing method based on spray granulation technology according to claim 1 is characterized in that: When preparing the mixed slurry, the mass ratio of material A, material B and water is 1:0.8-1.2:0.4-0.6 respectively.
8. The sagger manufacturing method based on spray granulation technology according to claim 1 is characterized in that: During the spray drying granulation process, the inlet air temperature of the spray dryer is controlled at 200°C-300°C, and the atomization pressure is controlled at 0.5-1.5MPa.
9. The sagger manufacturing method based on spray granulation technology according to claim 1, characterized in that: During high temperature sintering, the kiln temperature in the sintering stage is 1330-1390℃.
10. A positive electrode material sagger, characterized in that: The sagger is prepared by the sagger preparation method according to any one of claims 1 to 9.